Kesiapan Inovasi dan Kompetensi Wirausaha Dalam Mendorong Perilaku Kerja Inovatif: Studi Empiris pada Himpunan Pengusaha Muda Indonesia - Nalurani, Esti; Suhariadi, Fendy; Ng, Michelle (Universitas Negeri Malang, 2025)
The purpose of this study is to analyze the influence of self-confidence, entrepreneurial competence, and organizational support on the level of innovation readiness and innovative work behavior. This study used a quantitative approach with a survey method on members of the Indonesian Young Entrepreneurs Association. The results show that self-confidence and entrepreneurial competence have a positive influence on the level of innovation readiness and play a significant role in encouraging innovative work behavior. The level of innovation readiness has a positive effect on innovative work behavior, so that the higher the level of innovation readiness possessed by individuals, the greater the tendency to exhibit innovative work behavior. The level of innovation readiness is a mediating variable in the relationship between self-confidence and entrepreneurial competence variables and innovative work behavior. Conversely, the organizational support variable has a negative moderating effect, indicating that excessive facilitation can reduce individuals' intrinsic motivation to innovate.